The light in the ruins : a novel - Bohjalian, Chris, 1962- (Doubleday, 2013)
Hoping to safeguard themselves from the ravages of World War II within the walls of their ancient villa in Florence, the noble Rosati family become prisoners in their home when 18-year-old Cristina's courtship by a German lieutenant prompts the Nazis to take over the estate, a situation that leads to a serial murder investigation years later.